(untitled) (Research, Society and Development, 2022)
The performance of health professionals in interdisciplinary teams in primary health care of the Unified Health System gained prominence in Brazil, especially during the COVID-19 pandemic, a time when public health in the country collapsed, and there was a need of a greater number of professionals working in the area. In this sense, the objective of this study was to evaluate the impact that interdisciplinary participation had on care provided by health teams and on the clinical evolution of patients. Searches were carried out in the Virtual Health Library – VHL, which includes PubMed, SciELO and Lilacs, and in Google Scholar. A total of 285 articles were found, of which 44presented full text, and their abstracts were analyzed. Soon after, 13 texts were selected for analysis. It was observed that, in the articles investigated, teamwork has effectively contributed to the evolution of patients, and enabled the organization of health care in a perspective of expanded clinical practices centered on the individual, family and community.